Trend Media Sosial dalam Pendidikan Islam; Analisis tentang Model Pemanfaatannya - Salsabila, Unik Hanifah; Sari, Dwi Nur Indah; Sabilla, Rahma; Nurjanah, Aswin; Rasyid, Anggi Pratiwi (Sekolah Tinggi Agam Islam Sumatera Medan, 2022)
This study aims to analyze trends in the use of social media in Islamic education with a focus on three things: the types, benefits and models of using social media in Islamic religious education lessons. This research was conducted at Ibtidaiyah Madrasa Muhammadiyah Kenteng, which uses social media to support its daily learning. The two focus studies above were examined using qualitative research methods with a phenomenological approach. The research informants consisted of teachers as primary informants and school principals, parents and students as secondary informants. Data collection techniques using observation, interviews and documentation studies. The study results revealed that the types of social media users were Facebook, whats app, Instagram, and youtube. Facebook functions for friendship networks, then the whats app for group communication, then Instagram for sharing information, and YouTube for sharing learning videos. The benefit is as a medium to disseminate Islamic studies to students. The usage model is sharing information, assignments, references, and networking.